Controlled synthesis of SPION@SiO2 nanoparticles using design of experiments. Issue 14 (27th June 2022) - Harman, Clarissa L. G.; Mac Fhionnlaoich, Niamh; King, Aaron M.; Manning, Joseph R. H.; Lin, Wu; Scholes, Peter; Guldin, Stefan; Davies, Gemma-Louise
Abstract : A Design of Experiments approach was used to optimise synthesis of core@shell SPION@silica nanoparticles. Multiple linear regression analyses established relationships between the applied experimental variables and resulting particle properties. Abstract : The synthesis of single-core superparamagnetic iron oxide nanoparticles (SPIONs) coated with a silica shell of controlled thickness remains a challenge, due to the dependence on a multitude of experimental variables. Herein, we utilise design of experiment (DoE) to study the formation of SPION@SiO2 nanoparticles (NPs) via reverse microemulsion. Using a 3 3 full factorial design, the influence of reactant concentration of tetraethyl orthosilicate (TEOS) and ammonium hydroxide (NH4 OH), as well as the number of fractionated additions of TEOS on the silica shell was investigated with the aim of minimising polydispersity and increasing the population of SPION@SiO2 NPs formed. This investigation facilitated a reproducible and controlled approach for the high yield synthesis of SPION@SiO2 NPs with uniform silica shell thickness. Application of a multiple linear regression analysis established a relationship between the applied experimental variables and the resulting silica shell thickness. These experimental variables were similarly found to dictate the monodispersity of the SPION@SiO2 NPs formed. The overall population of single-core@shell particles was dependent on the interaction between the number of moles of TEOS and NH4 OH, with no influence from the number of fractionated additions of TEOS. This work demonstrates the complexity of the preparative method and produces an accessible and flexible synthetic model to achieve monodisperse SPION@SiO2 NPs with controllable shell thickness.